2012
DOI: 10.1016/j.fertnstert.2011.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Is PCOS an inflammatory process?

Abstract: PRO-- PCOS is associated with low-grade systemic inflammation as evidenced by elevation of multiple markers of inflammation such as C-reactive protein, interleukin-18, monocyte chemoattractant protein-1 and white blood count as well as endothelial dysfunction and increased oxidative stress. CON-- The evidence in support of the presence of chronic inflammatory state in the majority of women with PCOS is incontrovertible. It is apparent that PCOS is associated with a significant elevation of multiple markers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
173
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(189 citation statements)
references
References 65 publications
11
173
1
4
Order By: Relevance
“…Oxidative stress and chronic inflammation are closely inter-related. A vicious cycle exists whereby inflammation induces generation of ROS, while oxidative stress promotes and aggravates inflammation [23].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and chronic inflammation are closely inter-related. A vicious cycle exists whereby inflammation induces generation of ROS, while oxidative stress promotes and aggravates inflammation [23].…”
Section: Discussionmentioning
confidence: 99%
“…Fat accumulation on the trunk and in visceral depots has been reported in women with PCOS regardless of BMI [20]. The visceral adipocytes exert these effects in a paracrine and endocrine manner via the secretion of adipokines into the circulation, many of which increase inflammation [4,6]. The link between inflammation and metabolic disorders was first recognized by Hotamisligil et al who demonstrated that adipocytes express the pro-inflammatory cytokine TNF-α and TNF-α expression is markedly increased in adipocytes of obese mice [21].…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue is thought to play a key role in endocrine and metabolic control, creating a range of adipokines into the circulation, many of which increase inflammation [4]. Serum concentrations of high-sensitive C-reactive protein (hs-CRP), interleukin-18, monocyte chemoattractant protein-1 (MCP-1), and macrophage inflammatory protein-1a (MIP-1a) are found to be elevated in PCOS [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its etiopathophysiological core remains vague; however, gonadotropin-secretory alterations, androgen excess, insulin resistance and low-grade inflammation, in conjunction with the pivotal contribution of genetic and environmental parameters, are all involved in the interplay net of the syndrome (176,177). Recently, oxidative stress has also been highlighted as another potent modulator of PCOS (178,179).…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%